An Analysis of Javanese Registers in Traditional Markets - Cahya, Adellya Dwi; Aristiani, Dianita; Astuti, Indah Diah (TEKNOSASTIK, 2025)
This article discusses the exploration of Javanese language variation used in the context of traditional markets in Magelang City, Central Java, which focuses on register. The definition of the register itself is one of the linguistic phenomena where a word can have different meanings depending on the context or in a particular field. We conducted this research in one of the traditional markets in Magelang City, Central Java. This research was prepared using qualitative research with data collection methods of participatory observation and data analysis in the form of audio recordings containing interactions between sellers and buyers. In this case, this research used descriptive data analysis techniques to understand Javanese language variation and identify specific registers and contextual meaning in the context of traditional markets. From the result of the analysis, some specific registers were found, such as "timbang" which means "weighing goods" in the market, but if outside the market, it would mean "than." From this research activity, it was also found that the factors that influence the register are social status, age, and power relations. Sellers tend to use Javanese "Krama" for older buyers or those with higher status, while Javanese "Ngoko" is used in informal situations or for buyers they already know. This study also states that there is a language shift where sellers often switch to Indonesian when interacting with younger buyers because they know that many young people today cannot or do not understand Javanese. In addition to communication, the register used in the context of this traditional market can also reflect local culture, such as the example of the word "prepegan," which means the state of the market, which is very crowded on the eve of Eid. In conclusion, understanding the Javanese language register is very important to improve effective communication and prevent misunderstandings in transactions in traditional markets, while strengthening social relations in the community.  Keywords: communication, Javanese language, register, sociolinguistics, traditional market